2004
DOI: 10.1186/1471-2407-4-27
|View full text |Cite
|
Sign up to set email alerts
|

Expression of progesterone metabolizing enzyme genes (AKR1C1, AKR1C2, AKR1C3, SRD5A1, SRD5A2) is altered in human breast carcinoma

Abstract: Background: Recent evidence suggests that progesterone metabolites play important roles in regulating breast cancer. Previous studies have shown that tumorous tissues have higher 5α-reductase (5αR) and lower 3α-hydroxysteroid oxidoreductase (3α-HSO) and 20α-HSO activities. The resulting higher levels of 5α-reduced progesterone metabolites such as 5α-pregnane-3,20-dione (5αP) in tumorous tissue promote cell proliferation and detachment, whereas the 4-pregnene metabolites, 4-pregnen-3α-ol-20-one (3αHP) and 4-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 43 publications
(64 reference statements)
3
87
1
1
Order By: Relevance
“…Thus, AKR1C2 and possibly AKR1C1 may indirectly regulate the activity of the androgen receptor by promoting catabolism of DHT within prostatic cells, thereby modulating intracellular DHT levels. A similar finding was also observed in human breast cancer in which selective loss of AKR1C1, which reduces progesterone to the weak progestin 20␣-dihydroxyprogestgerone, was found in tumors compared with paired unaffected tissues (Ji et al, 2004;Lewis et al, 2004). Similar to prostate cancer, we predict that reduced AKR1C1 expression would also hinder progesterone metabolism, thereby augmenting the activity of the progesterone receptor (Ji et al, 2004).…”
supporting
confidence: 61%
“…Thus, AKR1C2 and possibly AKR1C1 may indirectly regulate the activity of the androgen receptor by promoting catabolism of DHT within prostatic cells, thereby modulating intracellular DHT levels. A similar finding was also observed in human breast cancer in which selective loss of AKR1C1, which reduces progesterone to the weak progestin 20␣-dihydroxyprogestgerone, was found in tumors compared with paired unaffected tissues (Ji et al, 2004;Lewis et al, 2004). Similar to prostate cancer, we predict that reduced AKR1C1 expression would also hinder progesterone metabolism, thereby augmenting the activity of the progesterone receptor (Ji et al, 2004).…”
supporting
confidence: 61%
“…RT-PCR analyses on tissues from 38 patients showed significantly higher levels of expression of 5a-reductase type 1 (SRD5A1) and 5a-reductase type 2 (SRD5A2) mRNA and significantly lower levels of expression of the 3a-HSO type 2 (AKR1C3), 3a-HSO type 3 (AKR1C2) and 20a-HSO (AKR1C1) mRNAs in the tumor tissues than in the normal tissues (Lewis et al 2004) (Fig. 4a).…”
Section: Changes In Expression Of Progesteronemetabolizing Enzymesmentioning
confidence: 99%
“…This is in marked contrast to the actions of P metabolites, where the 5a-pregnanes stimulate and the 4-pregnenes inhibit cell proliferation. Also, 5a-reductase type 2 (SRD5A2), which catalyzes J P Wiebe: Progesterone metabolites in breast cancer www.endocrinology-journals.org reduction of testosterone to DHT in androgendependent tissues such as the prostate, is present in very low levels in breast tissue (Ji et al 2004, Lewis et al 2004 and human breast cancer cell lines (Wiebe & Lewis 2003). In breast tissue, 5a-reductase type 1 (SRD5A1) is predominant and it may be that P is a better substrate than testosterone for this isoenzyme.…”
Section: Implications Of Changes In Progesterone 5a-reductase Activitmentioning
confidence: 99%
“…Of the three known isoforms, 5aR1 is expressed more frequently in the breast than 5aR2 and is considered the principal isoform (Suzuki et al 2001) despite its lower affinity for testosterone (Jin & Penning 2006), while 5aR3 has not been reported in the breast. The importance of 5aR1 in breast cancer development remains unclear, as either higher (Lewis et al 2004) or lower (Zhao et al 2010) levels of 5aR1 have been reported in tumour compared with matched normal tissues. However, a large number of studies suggest an inhibitory role for 5aR1 in disease progression.…”
Section: Endocrine-related Cancermentioning
confidence: 99%